O uso domiciliar de quimioterápicos orais e os desafios na saúde ambiental - Ferreira, Marco Aurélio Soares (2021)
Introduction: Oral chemotherapy drugs are increasingly present in the treatment of cancer, in this context, pharmacovigilance issues become very important. Health authorities should be aware of the risk of intoxication that these drugs offer to patients and family members, especially children, since in the oral pharmaceutical form, antineoplastic drugs are more available in the home environment. Another issue is about environmental risk, since it has been identified that the residues of these substances are emerging contaminants and their effects on the ecosystem are still poorly known. Objective: To investigate the possible toxicity risks that the use of oral chemotherapy in the home environment may cause to the environment and population. Methods: The study is an exploratory / descriptive and quantitative research. A bibliographic, descriptive, and integrative review type survey was carried out, as well as a documentary survey in the bularia and questionnaire application. Results: 15 substances with an endocrine-disrupting environmental character were identified, in adition to 11 others with a high toxic potential at the household level; whereas the integrative review pointed out that there are few studies and great challenges on the collective security of the Brazilian and worldwide population. With the questionnaire, it was argued that there is a lack of guidance for patients as to the dangers that chemotherapy can cause. Conclusion: It is noted that part of the drugs studied has great toxic and endocrine disrupting potential, so they can interfere in fauna and springs, altering the behavior of fish and other organisms living in this ecosystem and causing accidents. Thus, for confirmation purposes, ecotoxicity studies, isolated and specific to each substance, should be encouraged.